A process based approach software certification model for agile and secure environment - Mohamed, Shafinah Farvin Packeer (2015)
In today’s business environment, Agile and secure software processes are essential since they bring high quality and secured software to market faster and more cost effectively. Unfortunately, some software practitioners are not following the proper practices of both processes when developing software. There exist various studies which assess the quality of software process; nevertheless, their focus is on the conventional software process. Furthermore, they do not consider weight values in the assessment although each evaluation criterion might have different importance. Consequently, software certification is needed to give conformance on the quality of Agile and secure software processes. Therefore, the objective of this thesis is to propose Extended Software Process Assessment and Certification Model (ESPAC) which addresses both software processes and considers the weight values during the assessment. The study is conducted in four phases: 1) theoretical study to examine the factors and practices that influence the quality of Agile and secure software processes and weight value allocation techniques, 2) an exploratory study which was participated by 114 software practitioners to investigate their current practices, 3) development of an enhanced software process certification model which considers process, people, technology, project constraint and environment, provides certification guideline and utilizes the Analytic Hierarchy Process (AHP) for weight values allocation and 4) verification of Agile and secure software processes and AHP through expert reviews followed by validation on satisfaction and practicality of the proposed model through focus group discussion. The validation result shows that ESPAC Model gained software practitioners’ satisfaction and practical to be executed in the real environment. The contributions of this study straddle research perspectives of Software Process Assessment and Certification and Multiple Criteria Decision Making, and practical perspectives by providing software practitioners and assessors a mechanism to reveal the quality of software process and helps investors and customers in making investment decisions.